STRENGTH ANALYSIS OF CARGO-X UAV WING STRUCTURE USING SANDWICH COMPOSITE MATERIALS - Hartini, Dwi; Junaidin, Buyung; Habibi, Habibi (Institut Teknologi Dirgantara Adisutjipto, 2022)
The Cargo-X UAV aircraft is a UAV aircraft designed to carry medicines, packages and blood bags in areas that require fast and efficient handling. One of the important components of the Cargo-X UAV aircraft is the wing, so the strength of the wing structure must be seriously considered to ensure safety during flight under unexpected conditions. The purpose of this study was to analyze the wing structure of the UAV Cargo-X aircraft made of sandwich composite material to determine the level of safety of the wing structure. The loading of the wing structure uses the load due to the lift. The wing structure modeling uses CATIA software, while the analysis uses PATRAN/NASTRAN software. From the analysis results, the skin and spar wing structures are safe against loading, while the core section is not safe against loading.